Marketing Strategy Through Social Media Using Porter's Five Forces And SWOT Analysis Methods Case Study: Christina Ulos Indonesia - Rebecca Christina Pardede; Adelifa Situmorang; Rully Cesarlin Lumbanraja; Denis Saido Munthe; Santi Agustina Manalu; Rashmi Ranjan Panigrahi (International Journal of Management and Business Economics, 2026)
This study examines the development of social media–based marketing strategies for Christina Ulos, a traditional Batak ulos business, by integrating SWOT analysis and Porter’s Five Forces to understand its competitive position in the digital marketplace. Using a qualitative descriptive method with a participatory case study approach, data were collected through interviews, field observations, and supporting literature. The results show that Christina Ulos holds strong internal advantages, such as a long-standing reputation, authentic handwoven craftsmanship, deep cultural meaning in every motif, and a loyal customer base. However, challenges arise from limited production capacity, low digital literacy, and dependence on traditional sales channels. Externally, increasing public interest in local cultural products, government support for UMKM digitalization, and the growth of social media platforms offer significant opportunities. Yet, the presence of low-cost machine-made ulos, shifting consumer preferences, and intense digital competition pose substantial threats. The combined SWOT and Porter’s analyses highlight that social media marketing strategies should focus on cultural storytelling, consumer education about authentic handwoven ulos, optimization of high-quality visual content, marketplace integration, and influencer collaboration. This study concludes that an aggressive and adaptive digital marketing approach is essential for strengthening competitive advantage, expanding market reach, and preserving Batak cultural heritage in the modern digital environment